Enfermedad de Parkinson y demencia, calidad de vida y sobrecarga del cuidador: intervención multidisciplinaria en Atención Primaria - Rossón, Sebastián; Fuentealba, Claudia; Hormazábal, Cristián; Villena, Carolina; Brieba, Francisca (Revista Chilena de Salud Pública, 2013)
<!–[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> Introduction: Aims of the treatment of Parkinson’s disease and Dementia ar symptoms control, maintaining functionality and quality of life in both patients and caregivers, as well as preventing the burnout syndrome. Occupational Therapy and education seem to be useful. Aims of the study: Measure the effect of a multidisciplinary intervention in quality of life in both patients and caregivers, as well as on the caregiver’s burden. Materials and Methods: Quasi-experimental study, 29 patients with Parkinson’s Disease and/or Dementia, in Vitacura and their caregivers. Quality of life in patients and caregivers was measured with the WHOQOLBREF and SF-36 questionnaires respectively and the caregivers burden with the Zarit scale. A multidisciplinary intervention was conducted with educational sessions, selfhelp groups and integrative activities, Occupational therapy was carried out at home. Statistical analysis with SPSS® version 17. Results: Caregiver’s burden decreased significantly (Mean difference of 22 points Zarit scale, p < 0.001). No effect on quality of life of patients, except for a 22% decrease of satisfaction in the domain "social relationships" (p 0.001). Quality of life of caregivers increased significantly in the domain "Vitality" (p 0.006), with a trend towards improved satisfaction in the Mental Health Component (p 0.077). No differences in other domains. Discussion: Education and occupational therapy in the primary care setting contributes to improve vitality, helps to increase satisfaction in mental health of caregivers and alleviates the burden of care. The effect on quality of life of patients seems to be neutral. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>